Bird diversity in transition zone of Taka Bonerate, Kepulauan Selayar Biosphere Reserve, Indonesia - RADISTI A PRAPTIWI; RONNA SAAB; TATANG MITRA SETIA; GUSTI WICAKSONO; PRAWESTI WULANDARI; JITO SUGARDJITO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Praptiwi RA, Saab R, Setia TM, Wicaksono G, Wulandari P, Sugardjito J. 2019. Bird diversity in transition zone of Taka Bonerate, Kepulauan Selayar Biosphere Reserve, Indonesia. Biodiversitas 20: 819-823.   Conservation management in the buffer and transition zones of Biosphere Reserves play an important role in ensuring enhanced core zone protection. Tambolongan and Polassi are two islands located in the administrative region of South Sulawesi, Indonesia, and part of the transition zone area of UNESCO’s Taka Bonerate-Kepulauan Selayar (TBKS) Biosphere Reserve (BR). These two islands can be considered as some of the most populated islands in the region, containing a variety of human activities. These human activities, such as the ever expanding agriculture and the building of human habitation have put pressures toward ecosystem and species conservation in the BR. Bird are often the focus of conservation efforts, due to their roles in supporting the ecological functioning of their habitats. This study aims to provide baseline data of bird diversity in Tambolongan and Polassi that can be used as a proxy indicator of ecosystem health and input to conservation strategies within the BR area. A Visual Encounter Survey (VES) method is used to examine bird diversity index. Results from the observation recorded a total of 29 species were found in both islands, with 5 listed as protected species and 3 categorized as migratory species. The comparison between the two islands showed that the bird diversity index (H’) differs only slightly (H’Tambolongan=2.98; H’Polassi=2.71). This study provided the initial attempt in understanding the role of habitats or land cover types, guild types and human interferences in determining the diversity of bird population - and related ecosystem health - in the area. Such knowledge is essential in providing the information necessary for sustainable management practices. This work represents the first study to inventorize avian species diversity in the transition zone of TBKS BR.